Treatment outcomes of standard (high dose) cisplatin and non‐standard chemotherapy for locally advanced head and neck cancer. Issue 1 (6th July 2022) - Alamgeer, Muhammad; Coleman, Andrew; McDowell, Lachlan; Giddings, Charles; Safdar, Adnan; Sigston, Elizabeth; Wang, Yang; Subramaniam, Ashwin
Abstract: Introduction: Concurrent chemoradiotherapy with high‐dose (HD) cisplatin is the standard treatment for locally advanced head and neck squamous cell carcinoma (LA‐HNSCC). Due to the higher treatment‐related adverse effects with standard therapy, alternative regimens (non‐standard therapy), namely, lower dose weekly cisplatin, carboplatin/paclitaxel, or cetuximab are considered. There is, however, no consensus on non‐standard regimens. We aimed to investigate the efficacy and safety profile of these regimens. Methods: This single centre retrospective cohort study included all consecutive adult patients with newly diagnosed LA‐HNSCC treated with either standard or non‐standard regimens between January 2016 and April 2021. The primary outcome was 2‐year failure‐free survival (FFS). The secondary outcomes included acute toxicities, hospitalisation rates, dose modifications, treatment failure rates (TFR), and overall survival. Results: About 235 patients were included in the final analysis; median age was 61 years (IQR 55–67), and 87% were male. Most had oropharyngeal tumours (85.5%) and p16‐positivity was frequent (80%). About 56% received non‐standard regimens: weekly cisplatin = 79 and non‐cisplatin = 48. These patients had higher Charlson Comorbidity Index (CCI; p  < .001) and lower European Cooperative Oncology Group (ECOG)‐0 ( p  = .003). There was no difference in 2‐year FFS (hazard ratio [HR] = 1.16; 95% confidence interval – [CI] 0.65–2.05), hospitalisation and grade‐3 toxicity rates between the two regimens. Nausea and vomiting were lower in the non‐standard regimen (3.0% vs. 16%, p  < .001). Dose reductions, adjusted for age, sex, and CCI, were less likely in the non‐standard regimen (OR = 2.36; 95%‐CI: 1.01–5.49, p  = .007). Conclusions: We demonstrated similar efficacy of lower dose weekly cisplatin and carboplatin/paclitaxel regimens and better safety profile of weekly cisplatin compared to standard HD cisplatin regimens for LA‐HNSCC. Multicenter randomised control trials are required in HD cisplatin‐ineligible patients.